Development of Love and Faith in Teaching Profession Scale and Criterion - Porsiri, Nutnirun; Panya, Piyatida; Worakham, Paisarn (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were to 1) development of love and faith in teaching profession scale according to Item Responses Theory, 2) develop a cut score to create a criterion zone of love and faith in teaching profession score and evaluate a score of love and faith in teaching profession of educational students. Data were collected from 1,115 students in faculty of Education from 8 University in Thailand. Research instrument was love and faith in teaching profession scale with multiple choice in multi-level score. Data were analyzed including estimation 2 parameters of IRT. The cut-off scores of scales were developed using the criterion zone of the Wright map. Research findings were as follows: 1) There were 15 question accepted according to IRT parameter estimation criterion there were only 1 question with differential item function; 2) The criterion zone of love and faith in teaching profession score consisted 4 level as follows: level 4 faith in teaching profession score ( ) = -0.42 and upper, level 3 love in teaching profession score between ( ) = -3.25 ถึง -0.41, level 2 good attitude in teaching profession score ( ) = -4.95 ถึง -3.24, and level 1 non- love and faith in teaching profession score ( ) = -4.94 and lower; and 3) There were 70.40 percent of educational students had love and faith in teaching profession score in level 4 faith in teaching profession, 28.97 percent had love and faith in teaching profession score in level 3 love in teaching profession, and 0.63 percent had love and faith in teaching profession score in level 2 good attitude in teaching profession.